ESTIMASI MATRIKS ASAL TUJUAN PERJALANAN MENGGUNAKAN MODEL GRAVITY DENGAN FUNGSI HAMBATAN TANNER DI KOTA SURAKARTA - Niken Puspitasari; Syafi'i Syafi'i; Setiono Setiono (Program Studi Teknik Sipil FT UNS, 2014)
The research aimed to know the amount of estimation trip distribution models using the gravity method. In addition, to know the validation levelby comparing traffic flow resulted from the model and observation. This research was conducted in Surakarta as areas of studdy dividing the areainto 65 zone, 51 internal zone and 14 external zone. The road network that is analyzed is the arterial roads and collector roads. The methodwas used is gravity model as production and attraction constrained as estimation model MAT 2013 with EMME/3 software. On this modelthere are parameters ?that function as determinants of the magnitude of the spread of values that occur in each zone. Calibration method for obtainingparameters ?that are later used in the calculation of the estimated results of the MAT (obstacle function with Tanner) is the Newton-Raphson method of calibration. The calibration is done by a process of repetition until the convergence parameter value reaches the limit usingMatlab software application assistance. The Traffic volume values obtained by imposing a new matrix and incorporate current observations (trafficcount) to the road network by the method of loading User Equilibrium, is loading method which has the assumption that the total amount of thetrip will be entirely charged to all segments of the road network. Test Validation using the coefficient of Determination (R2). From the results ofcalculations with the help of Matlab is obtained by 0,0006. From the results of calculations with the help of EMME / 3, obtained by the totalnumber of movements in Surakarta is 35923.9 smp / hour. The level of validation (R2) is obtained by 0.77. Validation in the category of high,has 77% similarity with the original conditions on roads.